Impaired post-stroke collateral circulation in sickle cell anemia mice - Bian, Emily J.; Chen, Ching-Wen; Cheng, Chih-Mei; Kuan, Chia-Yi; Sun, Yu-Yo (Frontiers in Neurology, 2023)
Patients with sickle cell anemia (SCA) have a high incidence of ischemic stroke, but are usually excluded from thrombolytic therapy due to concerns for cerebral hemorrhage. Maladaptation to cerebral ischemia may also contribute to the stroke propensity in SCA. Here we compared post-stroke cortical collateral circulation in transgenic sickle (SS) mice, bone marrow grafting-derived SS-chimera, and wildtype (AA) controls, because collateral circulation is a critical factor for cell survival within the ischemic penumbra. Further, it has been shown that SS mice develop poorer neo-collateral perfusion after limb ischemia. We used the middle cerebral artery (MCA)-targeted photothrombosis model in this study, since it is better tolerated by SS mice and creates a clear infarct core versus peri-infarct area. Compared to AA mice, SS mice showed enlarged infarction and lesser endothelial proliferation after photothrombosis. SS-chimera showed anemia, hypoxia-induced erythrocyte sickling, and attenuated recovery of blood flow in the ipsilateral cortex after photothrombosis. In AA chimera, cerebral blood flow in the border area between MCA and the anterior cerebral artery (ACA) and posterior cerebral artery (PCA) trees improved from 44% of contralateral level after stroke to 78% at 7 d recovery. In contrast, blood flow in the MCA-ACA and MCA-PCA border areas only increased from 35% to 43% at 7 d post-stroke in SS chimera. These findings suggest deficits of post-stroke collateral circulation in SCA. Better understanding of the underpinnings may suggest novel stroke therapies for SCA patients.